Hepatitis C Vaccines, Antibodies, and T Cells - Shoukry, Naglaa H. (Frontiers in Immunology, 2018)
The development of vaccines that protect against persistent hepatitis C virus (HCV) infection remain a public health priority. The broad use of highly effective direct-acting antivirals (DAAs) is unlikely to achieve HCV elimination without vaccines that can limit viral transmission. Two vaccines targeting either the antibody or the T cell response are currently in preclinical or clinical trials. Next-generation vaccines will likely involve a combination of these two strategies. This review summarizes the state of knowledge about the immune protective role of HCV-specific antibodies and T cells and the current vaccine strategies. In addition, it discusses the potential efficacy of vaccination in DAA-cured individuals. Finally, it summarizes the challenges to vaccine development and the collaborative efforts required to overcome them.